Nutrition knowledge of elite and non-elite Gaelic footballers. Issue 2 (3rd April 2022) - Mitchell, Lachlan; Lehane, Paul; McCarthy, Mark; O'Shea, Kris; Tracey, Mark; Whyte, Taylor; Neville, Ross
ABSTRACT: Dietary intake plays a significant role in athletic performance and is influenced by several factors, including nutrition knowledge. Gaelic footballers are amateur athletes who conduct high-intensity, intermittent activity during training and competition, and have previously demonstrated insufficient dietary intake. This study aimed to examine nutrition knowledge in elite and non-elite Gaelic footballers. An online survey was distributed to competitive Gaelic footballers, examining nutrition knowledge using the Abridged Nutrition for Sport Knowledge Questionnaire. Total, general, and sport nutrition knowledge were compared between elite and non-elite athletes, and those who had and had not previously received nutrition education, using Mann-Whitney U-tests. A total of 190 participants (15.3% women) completed the survey. No differences between elite and non-elite athletes in nutrition knowledge were identified (p > 0.05). Athletes with previous nutrition education scored higher than those without previous nutrition education in total (54.0 ± 4.9% vs 46.8 ± 9.6%; p = 0.002) and sport (51.9 ± 12.5% vs 43.4 ± 11.8%; p = 0.005) nutrition knowledge. Findings suggest an importance of nutrition education at all levels of athletic competition to improve nutrition knowledge, which may empower athletes to make appropriate dietary decisions to support training and competition demands.